2015
DOI: 10.1242/jcs.166322
|View full text |Cite
|
Sign up to set email alerts
|

Lgr4 and Lgr5 drive the formation of long actin-rich cytoneme-like membrane protrusions

Abstract: Embryonic development and adult tissue homeostasis require precise information exchange between cells and their microenvironment to coordinate cell behavior. A specialized class of ultra-long actin-rich filopodia, termed cytonemes, provides one mechanism for this spatiotemporal regulation of extracellular cues. We provide here a mechanism whereby the stem-cell marker Lgr5, and its family member Lgr4, promote the formation of cytonemes. Lgr4-and Lgr5-induced cytonemes exceed lengths of 80 mm, are generated thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 61 publications
(63 reference statements)
3
40
0
Order By: Relevance
“…EMT has been proposed as a crucial process in tumor metastasis. Both cells at the tumor invasive front and circulating breast tumor cells express EMT markers (77,78), and inhibition of EMT impairs metastasis in mouse models (81). Among the transcription factors potentially driving EMT in breast cancer, we observed a significant decrease in SLUG and ZEB1 expression after LGR4 knockdown in vitro.…”
Section: Discussionmentioning
confidence: 75%
“…EMT has been proposed as a crucial process in tumor metastasis. Both cells at the tumor invasive front and circulating breast tumor cells express EMT markers (77,78), and inhibition of EMT impairs metastasis in mouse models (81). Among the transcription factors potentially driving EMT in breast cancer, we observed a significant decrease in SLUG and ZEB1 expression after LGR4 knockdown in vitro.…”
Section: Discussionmentioning
confidence: 75%
“…Recently, we demonstrated that vimentin-positive fibroblast cells remain within the stromal core of the FGP after Hh repression, in association with Hh-responding cells (38). Many of the vimentin-positive cells near the papilla basal lamina and epithelium have a migratory-like morphology, with numerous, long filopodia-like extensions that might be cytonemes or invadopodia (92). In other systems, both Shh-producing and responding cells extend long specialized filopodia that function in Shh signaling and trafficking Shh packaged in particles (93).…”
Section: Hedgehog Signaling In Taste Organ Stromamentioning
confidence: 99%
“…While signaling projections are common during development, it remains to be determined whether they are also frequently found in adult stem cells. However, in the murine gut, intestinal stem cells extend apical processes that reach in between neighbouring Paneth cells that constitute a key part of the intestinal stem cell niche (Barker et al, 2007) and Lgr4/5 has been shown drive formation of cytoneme-like projections in vitro (Snyder et al, 2015). It will be interesting to determine the role of these projections in stem cell signaling and whether cytocensors are found in other developmental contexts.…”
Section: Discussionmentioning
confidence: 99%